In Search of Distress Risk - CAMPBELL, JOHN Y.; HILSCHER, JENS; SZILAGYI, JAN (Journal of Finance, 2008)
ABSTRACTThis paper explores the determinants of corporate failure and the pricing of financially distressed stocks whose failure probability, estimated from a dynamic logit model using accounting and market variables, is high. Since 1981, financially distressed stocks have delivered anomalously low returns. They have lower returns but much higher standard deviations, market betas, and loadings on value and small‐cap risk factors than stocks with low failure risk. These patterns are more pronounced for stocks with possible informational or arbitrage‐related frictions. They are inconsistent with the conjecture that the value and size effects are compensation for the risk of financial distress.